SETTING STANDARD LEVELS FOR OBESITY AND CERTAIN PHYSICAL CAPABILITIES FOR FEMALE STUDENTS AT THE COLLEGE OF EDUCATION, UNIVERSITY OF KUFA - Iyad Al-Adhari, Rusul Alaa (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
Obesity, experienced by many, often results from a lack of nutritional awareness, excessive food intake, poor choice of food types, and low levels of effort and physical activity. We eat more than our bodies need and move little, leading to the storage of excess energy from food as fat, which accumulates in various parts of the body, Conclusions; There's a noticeable decrease in the Body Mass Index (BMI) variable among the research sample of female students, The research sample exhibits considerable weakness in the abdominal muscle endurance variable, The research sample performed well in the flexibility attribute, which was the best among the physical attributes under investigation.